The Easy Part of the Hard Problem: A Resonance Theory of Consciousness - Hunt, Tam; Schooler, Jonathan W. (Frontiers in Human Neuroscience, 2019)
Synchronization, harmonization, vibrations, or simply resonance in its most general sense seems to have an integral relationship with consciousness itself. One of the possible “neural correlates of consciousness” in mammalian brains is a specific combination of gamma, beta and theta electrical synchrony. More broadly, we see similar kinds of resonance patterns in living and non-living structures of many types. What clues can resonance provide about the nature of consciousness more generally? This paper provides an overview of resonating structures in the fields of neuroscience, biology and physics and offers a possible solution to what we see as the “easy part” of the “Hard Problem” of consciousness, which is generally known as the “combination problem.” The combination problem asks: how do micro-conscious entities combine into a higher-level macro-consciousness? The proposed solution in the context of mammalian consciousness suggests that a shared resonance is what allows different parts of the brain to achieve a phase transition in the speed and bandwidth of information flows between the constituent parts. This phase transition allows for richer varieties of consciousness to arise, with the character and content of that consciousness in each moment determined by the particular set of constituent neurons. We also offer more general insights into the ontology of consciousness and suggest that consciousness manifests as a continuum of increasing richness in all physical processes, distinguishing our view from emergentist materialism. We refer to this approach, a meta-synthesis, as a (general) resonance theory of consciousness. We offer some suggestions for testing the theory.